A located and user personalized event's dissemination platform - Costa-Dasilva, Juan Ignacio; Gómez-Rodríguez, Alma; González-Moreno, Juan C.; Ramos-Valcárcel, David (Journal of intelligent & fuzzy systems, 2015)
Ambient Intelligence has emerged lately as the integrating concept which includes Ubiquitous Computing, Ubiquitous Communication and Intelligent User Interfaces. The real implementation of such concepts is based on the use of new technology and innovative ways of development. Agent Oriented Software Engineering techniques and concepts have been used as a way of providing support to ubiquitous computing and communication. In addition, intelligent user interfaces require systems that provide a more efficient and rich interface with the user than the traditional ones. This paper presents a platform called MAPAS, which uses Ambient Intelligence concepts and techniques to give a fully scalable solution to a particular problem. The chosen system provides a solution, using the platform, to personalize the dissemination of events, that is, the system makes available to the user a set of events of his/her interest. This kind of systems requires a high degree of user's personalization. However nowadays, it is the user who must search the events of interest or subscribe to several different services or pages. The platform introduced in this paper takes profit of Agent Oriented technology to provide a system composed of various agents who may run in different devices, which communicate and provide a user personalized selection of events. Moreover, the system is aware of the surrounding environment, can be installed on smart devices, provides a rich and intuitive user interface and uses Augmented Reality techniques to give spatial location data about the events. Regarding the characteristics of the solution, it seems to be suitable for problems in the domain of Ambient Intelligence.